2002
DOI: 10.3168/jds.s0022-0302(02)74176-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactoferrin in Combination with Penicillin on the Morphology and the Physiology of Staphylococcus aureus Isolated from Bovine Mastitis

Abstract: The objective of the present study was to evaluate the therapeutic potential of bovine lactoferrin or lactoferricin in combination with penicillin G against Staphylococcus aureus. Minimal inhibitory concentrations of lactoferrin, lactoferricin, penicillin, and combinations of lactoferrin or lactoferricin with penicillin were determined for 15 S. aureus strains including several strains resistant to beta-lactam antibiotics. The fractional inhibitory concentration index indicated a synergistic effect between lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 30 publications
3
51
0
1
Order By: Relevance
“…The bactericidal and synergistic effects of bLf in combination with penicillin G on the growth of S. aureus was evaluated. Additionally, alterations in bacterial structure were observed with bLf, similar to those observed with high concentrations of penicillin G alone [36]. In addition, it was reported that apobLf could inhibit the growth of S. aureus; the results served as experimental evidence for further in vivo research [37].…”
Section: In Vitro Assaysmentioning
confidence: 70%
“…The bactericidal and synergistic effects of bLf in combination with penicillin G on the growth of S. aureus was evaluated. Additionally, alterations in bacterial structure were observed with bLf, similar to those observed with high concentrations of penicillin G alone [36]. In addition, it was reported that apobLf could inhibit the growth of S. aureus; the results served as experimental evidence for further in vivo research [37].…”
Section: In Vitro Assaysmentioning
confidence: 70%
“…40 Diarra et al reported that LF induced a weak cell wall increase in cell permeability by showing that LF decreased the synthesis of peptidoglycans, which are important components of the cell wall. 41,42 Also, Nibbering et al reported that LF also has intracellular activities that result in disruption of the metabolic activity and subsequent death of bacteria. 37 As our results show, the cell membrane of grampositive S. gordonii in LF and LF-AS groups is damaged [Figs.…”
Section: B Inhibition Of S Gordonii Adhesion and The Bactericidal Ementioning
confidence: 99%
“…Esta proteína possui capacidade bacteriostá-tica, principalmente, por tornar os níveis de ferro na glân-dula mamária indisponíveis (Green et al 2002, Kutila et al 2003, Chaneton et al 2008. Estudos realizados por Diarra et al (2002) indicam, ainda, uma potente atividade bactericida da lactoferrina por meio do aumento da permeabilidade da membrana celular bacteriana e lesão da parede celular externa, particularmente, em bactérias Gram-negativo, podendo aumentar o efeito de alguns antimicrobianos. Este fato pode justificar os resultados aqui apresentados, nos quais nota-se a ocorrência de diminuição na porcentagem de vacas infectadas no grupo de vacas não vacinadas (J5Vcont), ainda que menos acentuada quando comparadas às vacinadas (J5V), podendo-se atribuí-la ao aumento na taxa de cura espontânea dos animais, presente no perí-odo seco pela ação da lactoferrina, bem como outros fatores imunológicos inerentes ao animal nesta fase fisiológica (Burvenich et al 2007), associada à terapia de vacas secas.…”
Section: Resultsunclassified